Evaluation of stereoscopic visual fatigue in experts. Issue 8 (12th March 2015) - Wang, Danli; Qi, Yunfeng; Wang, Tingting; Qiao, Heng; Shi, Yining; Zhang, Lan
Abstract: Several objective or subjective measures have been employed to evaluate stereoscopic visual fatigue. Objective measures are more preferred for their capability to quantify the degree of human visual fatigue without being affected by individual variation. However, the combination of objective indicators, their sensibility in reflecting subjective fatigue and their applicability to different groups has rarely been studied. In our previous study based on non‐expert experiment, we proposed a method combining subjective assessment and objective measures to evaluate stereoscopic visual fatigue and an objective visual fatigue model (non‐expert model). In this study, we use the same procedure to conduct a contrast experiment in 2D and 3D conditions, but only with expert viewers. The results in 2D condition show that the two objective indicators are usable for visual fatigue evaluation. The difference between the results in 2D and 3D conditions shows that the stereo 3D can cause much more fatigue and the indicators can efficiently identify the extra fatigue with satisfactory accuracy. An objective visual fatigue model (expert‐only model) is developed based on the data obtained in the 3D condition and is evaluated with comparison to the non‐expert model. Both visual fatigue models show high correlation with the subjective data. The method we proposed is reasonably insusceptible to different viewer groups, and the results of repeated experiments are consistent. It is a promising approach to evaluate visual fatigue efficiently and objectively. Abstract : Several objective or subjective measures have been employed to evaluate stereoscopic visual fatigue. Objective measures are more preferred for their capability to quantify the degree of human visual fatigue without being affected by individual variation. However, the combination of objective indicators, their sensibility in reflecting subjective fatigue and their applicability to different groups has rarely been studied.